2016
DOI: 10.1007/s11356-016-6657-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the variation of carbonyl compounds concentrations before, during, and after the renovation of an apartment at Niterói, Brazil

Abstract: The present work reports the variation of 31 carbonyl compounds (CC) in an apartment located at Niterói City, Rio de Janeiro State, Brazil. Eight sampling campaigns were conducted through a 1-year period, and three areas (living room, kitchen, and bedroom) were evaluated before, during, and after the renovation activities and reoccupation of the apartment. Samples were collected using SEP-PAK cartridges impregnated with 2,4-dinitrophenylhydrazine, and the hydrazones were analyzed using rapid resolution liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Likewise, propylene glycol increased after application of the wall paint and benzene after introduction of some furniture. 29 Ochs et al 30 identified that the door varnishing was responsible for a high emission of butanone and other carbonyl compounds. Plaisance et al 31 measured the emissions of VOCs at six construction stages in three energy-efficient timber frame houses and found that high m,p-xylenes and ethylbenzene concentrations at the time of the structural work were due to the emission from the polyurethane adhesive mastic used as a sealing material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, propylene glycol increased after application of the wall paint and benzene after introduction of some furniture. 29 Ochs et al 30 identified that the door varnishing was responsible for a high emission of butanone and other carbonyl compounds. Plaisance et al 31 measured the emissions of VOCs at six construction stages in three energy-efficient timber frame houses and found that high m,p-xylenes and ethylbenzene concentrations at the time of the structural work were due to the emission from the polyurethane adhesive mastic used as a sealing material.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, propylene glycol increased after application of the wall paint and benzene after introduction of some furniture 29 . Ochs et al identified that the door varnishing was responsible for a high emission of butanone and other carbonyl compounds 30 .…”
Section: Introductionmentioning
confidence: 99%
“…As it was reported (Emri et al 2004), even very low concentrations of this aldehyde (<10 −4 M) causes DNA damage in human skin cells. The environmental occurrence of formaldehyde is caused by the anthropogenic and nonanthropogenic organic matter oxidation processes, by the release from resins and from other products, to which it is usually added as a preservative (Barker et al 1996;Salthammer et al 2010;Madureira et al 2016;Ochs et al 2016). One of the possible natural routes of formaldehyde entrance into the environment is through biochemical Oand N-demethylation being a part of metabolic conversions occurring in living organisms (Kalász 2003;Hagel and Facchini 2010;Farrow and Facchini 2013).…”
Section: Introductionmentioning
confidence: 99%